Pengaruh Lingkungan Kerja dan Kompetensi Guru terhadap Motivasi dan Dampaknya terhadap Kinerja Guru pada Sekolah Menengah Kejuruan Negeri di Kabupaten Muaro Jambi - Bukri Bukri; Arna Suryani; Sudirman Sudirman (Universitas Batanghari, 2023)
The purpose of this study is to describe the working environment, skills, motivation and performance of professional teachers under Regent Muaro Jambi. Next, analyze the influence of the teacher's work environment and skills on motivation, analyze the impact of the teacher's work environment and skills on the teacher's performance, and then analyze the influence of motivation on teacher performance, then analyze the influence of the work environment and teachers. attitude. skill. by motivating teachers to perform. This research is a study that uses descriptive and verifiable research methods, specifically the method of investigating a group of people, an object, a situation and the state of a thinking system in order to describe a systematic pictures according to reality. have learned. . The verification study aims to test the hypothesis about the influence of the variables in this study. This study involved all the productive professional teachers of SMKN Muaro Jambi, a total of 150 teachers. A sample of 60 respondents was based on Slovin's formula with 1% confidence. Data were analyzed using SPSS.22. The results show that the working environment is good, the teacher's capacity is high, the work motivation is high, the teacher's work efficiency is also high, the working environment and teacher's capacity are improved, and there are impact on and right . positive and significant impact on motivation, work environment and teachers. Simultaneous and partial skills have a positive and significant impact on teacher performance and motivation has a positive and significant impact on teacher performance at SMKN Muaro Jambi Regency.